Pemberdayaan Perempuan dalam Pengembangan UMKM: Studi Kasus Produk Lokal “Mie Des” di Dusun Klisat Kalurahan Srihardono Kecamatan Pun dong Kabupaten Bantul - Uskha Dyah Arsanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to describe the form of women's empowerment in the development of Micro, Small, and Medium Enterprises (MSMEs) through a case study of the local product business